Storage of markies cultivar potatoes for prossessing - de Oliveira Salomão Petrucci, Kharen Priscilla; Mota Pereira, Ariana; Alvarenga Moreira, Marialva; Cecon, Paulo Roberto; Finger, Fernando Luiz (Revista Ceres, 2025)
The refrigerated induce the sweetening of the potato, which results in the dark color. The objective of this study was to determine the temperature and shelf life of Markies potato tubers under refrigerated storage for the processing of French fries. The levels of total soluble sugar (TSS), reducing sugars (RS), peroxidase (POD) and polyphenoloxidase (PPO) activity, color after frying and start of sprout were determined. The accumulation of TSS started at 30 days in the tubers at 4 and 5 °C and in the tubers at 6 and 8 °C, at 150 days. The activity of POD and PPO were not influenced by temperature or storage time. Tubers at 4 e 5 °C showed higher TSS and RS contents and darker color after frying than tubers stored at 6 and 8 °C which had their color maintained within the industry-acceptable standard up to 240 days of storage. Temperatures of 4 and 5 °C delayed the onset of sprouting, starting at 150 days, and at temperatures of 6 and 8 °C, the onset of sprouting occurred from 90 and 60 days of storage, respectively. It is concluded that the cultivar Markies should be stored at 6 °C for 240 days.